Effects of neuromuscular training on the rear-foot angle kinematics in elite women field hockey players with chronic ankle instability - Kim, E.; Choi, H.; Cha, J.-H.; Park, J.-C.; Kim, T. (Journal of Sports Science & Medicine, 2017)
The aims of this study were to investigate the ankle position, the changes and persistence of ankle kinematics after neuromuscular training in athletes with chronic ankle instability (CAI). A total of 21 national women`s field hockey players participated (CAI = 12, control = 9). Ankle position at heel strike (HS), midstance (MS), and toe touch (TT) in the frontal plane during walking, running and landing were measured using 3D motion analysis. A 6-week neuromuscular training program was undertaken by the CAI group. Measurements of kinematic data for both groups were measured at baseline and the changes in kinematic data for CAI group were measured at 6 and 24 weeks. The kinematic data at HS during walking and running demonstrated that the magnitude of the eversion in the CAI group (-5.00° and -4.21°) was less than in the control group (-13.45°and -9.62°). The kinematic data at MS also exhibited less ankle eversion in the CAI group (-9.36° and -8.18°) than in the control group (-18.52° and -15.88°). Ankle positions at TT during landing were comparable between groups. Following the 6-week training, the CAI participants demonstrated a less everted ankle at HS during walking and running (-1.77° and -1.76°) compared to the previous positions. They also showed less ankle eversion at MS (-5.14° and -4.19°). Ankle orientation at TT changed significantly to an inverted ankle position (from -0.26° to 4.11°). The ankle kinematics were restored back to the previous positions at 24 weeks except for landing. It appeared that athletes with unstable ankle had a relatively inverted ankle position, and that 6-week neuromuscular training had an immediate effect on changing ankle orientation toward a less everted direction. The changed ankle kinematics seemed to persist during landing but not during walking and running